Microstructure analysis, physical and thermal properties of Al2O3-Al2TiO5 functionally graded ceramics for the application of car brake rot - Rong Kimberly, F.; Oo, Z.; Debnath, Sujan (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2015)
Aluminium titanate (AT) (Al 2 TiO 5) is a promising engineering material because of its low thermal expansion coefficient, excellent thermal shock resistance, good refractoriness and non-wetting with most metals. Functionally graded material (FGM) is generally a particulate composite with continuously varying volume fractions. FGMs are alternative materials for dental implants, building materials and ballistic protection. It has been of great interest to future engines, internal combustion engines, metal cutting and other high temperature engineering application. There has been a demand for an adequate disc brake that requires less maintenance in the automotive manufacturing industry. FGM, the next evolution of layered structure, consists of graded compositions that are dispersed across the ceramic which produces a gradual improvement in the properties across the ceramic at a steady pace.